Association of presurgical circulating MicroRNAs with 1-year postsurgical pain reduction in spine facet osteoarthritis patients with lumbar spinal stenosis. Issue 3 (September 2022) - Lively, Starlee; Milliot, Marie; Potla, Pratibha; Espin-Garcia, Osvaldo; Layeghifard, Mehdi; Sundararajan, Kala; Endisha, Helal; Nakamura, Akihiro; Perruccio, Anthony V.; Veillette, Christian; Kapoor, Mohit; Rampersaud, Y. Raja
Abstract: Purpose: Up to 30% of spine facet osteoarthritis patients with lumbar spinal stenosis (SF-OA ​+ ​LSS) have little to no improvement in their pain after surgery. Lack of meaningful improvement in pain following surgery provides a unique opportunity to identify specific predictive biomarker signatures that might be associated with the outcomes of surgical treatment. The objective of the present study was to determine whether a microRNA (miRNA) biomarker signature could be identified in presurgical blood plasma that corresponded with levels of SF-OA ​+ ​LSS patient post-surgical pain intensity one year later. Methods: RNA was extracted from baseline plasma of SF-OA ​+ ​LSS patients and prepared for miRNA sequencing. Statistical approaches were performed to identify differentially expressed miRNAs associated with reduced 1-year postsurgical pain (n ​= ​56). Using an integrated computational approach, we further created predicted gene and pathway networks for each identified miRNA. Results: We identified a panel of 4 circulating candidate miRNAs (hsa-miR-155-5p, hsa-let-7e-5p, hsa-miR-125a-5p, hsa-miR-99b-5p) with higher levels at presurgical baseline that were associated with greater changes in % NPRS20Δ, reflecting reduced pain intensity levels at one year. Genes encoding hsa-let-7e-5p, hsa-miR-125a-5p, and hsa-miR-99b-5p are part of an evolutionarily conserved miRNA cluster. Using integrated computational analyses, we showed that mammalian target of rapamycin, transforming growth factor-β1 receptor, Wnt signaling, epithelial–mesenchymal transition regulators, and cholecystokinin signaling were enriched pathways of predicted gene targets. Conclusions: Taken together, our findings suggest that 4 presurgical baseline circulating miRNAs correlate with 1-year postsurgical SF-OA ​+ ​LSS patient pain intensity and represent possible candidate biomarker signature of surgical pain response.